LYSINIBACILLUS XYLANILYTICUS., A NOVEL BACTERIAL STRAIN ISOLATED FROM SOIL WITH FIBRINOLYTIC ACTIVITY - RESHMA C V; FATHIMATHU ZUHARA K (International Journal of Pharma and Bio Sciences, 2013)
A novel fibrinolytic enzyme producing bacteria was isolated and identified by morphological and biochemical characteristics and confirmed by 16S r DNA as Lysinibacillus xylanilyticus. The optimum conditions for enzyme production was determined by response surface methodology instead of one factor at a time method. Placket burman method was used for the initial screening process. In our study the newly isolated strain Lysinbacillus xylanyliticus was found to produce fibrinolytic enzyme (2468.713U/ml) using the statistically optimized media which contain glucose, soy peptone, magnesium sulphate and ammonium nitrate as components.